2004
DOI: 10.1179/027249304225013349
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder and urinary tract precipitations associated with ceftriaxone therapy in children: a prospective study

Abstract: The incidence and outcome of gallbladder and urinary tract complications in children receiving ceftriaxone therapy were evaluated prospectively. The subjects were given intravenous ceftriaxone, 100 mg/kg/day, in two divided doses infused over 20-30-minute periods, for 5-14 days. Serial abdominal ultrasonography revealed gallbladder and urinary tract precipitations in five of 35 children, three of whom had gallbladder pseudolithiasis, one gallbladder sludge and one gallbladder pseudolithiasis and urinary bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…While various researchers have drawn a connection between high doses (>100 mg/kg daily) during extended treatment periods with the development of urinary stones [1,5,12], this problem also occurs at normal dose levels [6,8]. In agreement with these findings, we failed to show a strong relationship between ceftriaxone dose and the uCa/ Cr.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…While various researchers have drawn a connection between high doses (>100 mg/kg daily) during extended treatment periods with the development of urinary stones [1,5,12], this problem also occurs at normal dose levels [6,8]. In agreement with these findings, we failed to show a strong relationship between ceftriaxone dose and the uCa/ Cr.…”
Section: Discussioncontrasting
confidence: 61%
“…As an anion, ceftriaxone readily forms an insoluble salt with calcium in a 1:1 molar ratio that is capable of precipitation once the solubility of the salt is exceeded [6,[10][11][12]. These biochemical characteristics of ceftriaxone treatment frequently cause biliary sludge or pseudolithiasis, a well-known side effect in children [2][3][4][5]. This complication may develop after 2-16 days of treatment initiation [4-6, 13, 14] and is characterized by asymptomatic biliary changes; in most cases, it is reversible [3,13].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Contrary to biliary pseudolithiasis caused by cephtriaxone treatment, the pathogenesis of urinary stones of the same origin has still remained far less satisfactorily explained [2][3][4][5][6][7]. Some investigations point to possible association with increased urinary calcium excretion, although majority of reports declare unclear results.…”
Section: Introductionmentioning
confidence: 99%
“…All stones were small (2 mm) and disappeared spontaneously in three cases. Arcun et al, in their series of 35 children treated with CTX, demonstrated gallbladder precipitation in five children; only one of these had associated urinary bladder sludge [3].Risk factors for CTX-induced urolithiasis are positive familiar history, high CTX dose, rapid infusion rate, dehydration and combination with nephrotoxic drugs [1,8,9,10,11]. Although biliary and urinary tract CTX precipitations are mainly asymptomatic and reversible, patients at risk should have routine ultrasound examination during CTX therapy.…”
mentioning
confidence: 97%